2019
DOI: 10.1111/jcmm.14698
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of ZFAS1 indicates dismal prognosis for cholangiocarcinoma and promotes proliferation and metastasis by modulating USF1 via miR‐296‐5p

Abstract: LncRNAs has been demonstrated to modulate neoplastic development by modulating downstream miRNAs and functional genes. In this study, we aimed to detect the interaction among lncRNA ZFAS1 miR‐296‐5p and USF1. We explored the proliferation, migration and invasion of cholangiocarcinoma. The differentially expressed ZFAS1 was discovered in both tissues and cell lines by qRT‐PCR. The targeting relationship between miR‐296‐5p and ZFAS1 or USF1 was validated by dual‐luciferase assay. The impact of ZFAS1 on CCA cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Based on the above results, we found that the up-regulation of HAS2-AS1 was related to the development of glioma, thus, it is necessary to explore the underlying molecular mechanism. Several studies have demonstrated that lncRNAs can be activated by their upstream transcription factors [15,19,20]. The transcription factors that regulate the expression of HAS2-AS1 were predicted through the hTFtarget database, and USF1 was selected as the object.…”
Section: Usf1 Activates the Expression Of Has2-as1 By Binding To The mentioning
confidence: 99%
“…Based on the above results, we found that the up-regulation of HAS2-AS1 was related to the development of glioma, thus, it is necessary to explore the underlying molecular mechanism. Several studies have demonstrated that lncRNAs can be activated by their upstream transcription factors [15,19,20]. The transcription factors that regulate the expression of HAS2-AS1 were predicted through the hTFtarget database, and USF1 was selected as the object.…”
Section: Usf1 Activates the Expression Of Has2-as1 By Binding To The mentioning
confidence: 99%
“…The included 2263 patients all come from China. 16 types of tumors were included in this study, which contains pancreatic adenocarcinoma (PAAD) [10], hepatocellular carcinoma (HCC) [11,18], melanoma [12], esophageal squamous cell carcinoma (ESCC) [13,19], hepatoblastoma (HB) [20], cholangiocarcinoma (CCA) [14], papillary thyroid carcinoma (PTC) [21], prostate cancer (PCa) [22], clear cell renal cell carcinoma (ccRCC) [15], colorectal cancer (CRC) [16,23,24], bladder cancer [25,26], nasopharyngeal carcinoma (NPC) [27], gastric cancer (GC) [28], epithelial ovarian cancer (EOC) [29], non-small cell lung cancer (NSCLC) [30], glioma [31]. ZFAS1 expression in tumor tissues were all detected by qRT-PCR.…”
Section: Details Of Included Studymentioning
confidence: 99%
“…Growing studies have reported abnormal expression of ZFAS1 in diverse cancers, including pancreatic cancer [10], hepatocellular carcinoma [11], melanoma [12], esophageal squamous cell carcinoma [13] and so on. Moreover, elevated ZFAS1 expression is reported to be related to poor prognosis and clinical characteristics in various cancers [14][15][16], which indicate that ZFAS1 may serve as a promising biomarker for the prognosis and therapy of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers have become very interested in their role in tumour invasion, metastasis, and signalling pathways, and previous studies have demonstrated the involvement of lncRNAs as key molecules in the malignant biology of various cancers [ 8 – 10 ]. At present, some studies have described the relevant roles of fractional lncRNAs in cholangiocarcinoma [ 11 13 ], but the role of more lncRNAs in the malignant progression of intrahepatic cholangiocarcinoma still needs to be further identified and analysed.…”
Section: Introductionmentioning
confidence: 99%